Creating healthy workplaces in healthcare: Are we delaying progress by focusing on what we can do rather than what we should do? - Montgomery, Anthony; Lainidi, Olga (Frontiers in Public Health, 2023)
All the available evidence points to the fact that healthcare is under considerable stress, and while change is urgently needed there is no quick fix; systemic and sustained changes in organizational cultures within healthcare are required. Moreover, the fragility of healthcare systems globally has been starkly exposed by the Coronavirus 2019 pandemic. We have gathered enough evidence to know what is driving poor wellbeing, and how these processes impact on quality of care and patient safety. Indeed, we have a good idea of what we need to do to improve the situation. Therefore, this begs a simpler question; If we know how to create healthy workplaces, why is it so difficult to achieve this in healthcare? In the following perspective paper, we will argue that we can do better if we address the following three issues: (1) we are ignoring the real problems, (2) limited successes that we are achieving are moving us further from tackling the real problems, (3) culture change is accepted as crucial, but we are not accepting what the evidence is telling us about healthcare culture. Tackling burnout is useful and necessary, but we must increase dignity among healthcare employees. Moreover, we need to train line managers to recognize and facilitate the need of employees to feel competent and be appreciated by others, while helping them set wellbeing boundaries.